Ananlisis kemampuan komunikasi matematis ditinjau dari self-efficacy siswa - Lovita Fauziah; Heni Pujiastuti; Nurul Anriani (Universitas Sultan Ageng Tirtayasa, 2023)
Mathematical communication ability is an essential part of mathematic and mathematic education. This mathematical communication is useful for students to turn an idea into an object of thought. Beside that, one of the psychological or affective aspects is self-efficacy. The purpose of this study was to describe the extent to which a person's self-efficacy can determine students' mathematical communication ability, especially in junior high school. This research was conducted in the odd semester of the 2020/2021 school year at SMP Negeri 1 Cilegon.The research subjects in this study were 20 students of class VIII E based on the high, medium and low self-efficacy categories for conducting tests and interviews.